2015
DOI: 10.4103/0255-0857.148381
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Scrub typhus at a tertiary care hospital in Andhra Pradesh

Abstract: Scrub typhus should be included in the differential diagnosis of fever of unknown origin along with dengue, malaria and leptospirosis which are the other common endemic infections in this part of the country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 16 publications
2
19
1
Order By: Relevance
“…It has a high sensitivity (99 %), specificity (96 %) and serological agreement (97.5 %) with immunofluorescent assay [ 13 ]. A correlation of 97 %, between IgM ELISA and SD Bioline Tsutsugamushi rapid diagnostic test, was reported by Ramyasree A et al [ 14 ] among 100 suspected cases of scrub typhus in India.…”
Section: Methodsmentioning
confidence: 81%
See 2 more Smart Citations
“…It has a high sensitivity (99 %), specificity (96 %) and serological agreement (97.5 %) with immunofluorescent assay [ 13 ]. A correlation of 97 %, between IgM ELISA and SD Bioline Tsutsugamushi rapid diagnostic test, was reported by Ramyasree A et al [ 14 ] among 100 suspected cases of scrub typhus in India.…”
Section: Methodsmentioning
confidence: 81%
“…Fever of >12 days, presence of eschar, ICU admission, shock needing ionotropes, CNS dysfunction etc. have also been proven to be predictors of mortality [ 5 , 14 , 35 ]. These give valuable hints to the impending fatal outcome and may help the clinicians to initiate the intensive management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported seroprevalence of O . tsutsugamushi for each country is shown in Table 1 [ 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 ]. The reports of outbreaks of scrub typhus are summarized in Table 2 [ 43 , 94 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , …”
Section: Methodsmentioning
confidence: 99%
“…In the present study the eschar was found in 7.69% of the patients which was very low in comparison to 41.7%, 46% from studies done by Dass et al at Meghalaya [12] and M. Vivekanandan et al [1] at Pondicherry, while most studies of the Oriental countries had eschar in 60-70% patients. Recent studies from northern India [17,18] and southern India [19,20,21] have also the similarly low level of prevalence of Eschar in their populations.…”
Section: Discussionmentioning
confidence: 96%